Scarring effects of the first labour market experience: A sibling based analysis - Oskar Nordström Skans (Institute for Labour Market Policy Evaluation (IFAU), 2004)
The paper studies the relationship between teenagers first labour market experience and subsequent labour market performance using data on all Swedish youths graduating from vocational high school programmes in 199194. Sibling fixed-effects combined with detailed data on high school programmes, grades and work experience during high school are used in order to identify the causal long-run effects of experiencing unemployment subsequent to graduation. The results show a 3 percentage-points increase in the unemployment probability and a 17 % reduction in annual earnings after 5 years due to post-graduation unemployment. The results thus show that teenage labour market failure is in fact costly even though most teenagers have relatively short unemployment spells.
Keywords: J64; 330; Youth unemployment; scarring; state dependence; siblings